The last royal epoch: New Zealand Interior and Landscape Architecture in the 1900s - McCarthy, Christine (Architectural History Aotearoa, 2025)
King Edward VII (reign 1901-10) was - as Douglas Lloyd Jenkins observes - "the last British monarch to give his name to a decorative epoch." As the British royals loosened their grip on aesthetic terminology, New Zealand also took the step of discarding colonialism for dominionship in 1907 - after saying "no thanks" to becoming the seventh Australian state when the colonies of New South Wales, Victoria, Queensland, Tasmania, Western Australia, South Australia federated in January 1901. While we rejected Australia, we annexed the Cook Islands and Niue that same year. Smith writes that "Islander chiefs favoured annexation on the understanding that land rights would be preserved, though they too lost control." This first decade of the twentieth century thus built on Pākehā awareness in the 1890s of "a local, rather than solely a global past. The death of the first generation of pioneers, combined with the statistical knowledge that most New Zealanders were now born here, added up to the idea that a distinctive New Zealander might exist."